A Cultural Content Analysis of English Textbooks Written by Native and Non-native Speakers - Ichsan Fauzi Pangestu; Henny Soepriyanti; Arafiq Arafiq; Untung Waluyo (CV. Alim's Publishing, 2023)
The examination of cultural content in textbooks enables educators to identify suitable course materials that effectively cater to the linguistic requirements of learners in a culturally appropriate manner. This study aimed to examine the cultural aspects of the target language in high school English textbooks, specifically